Applying sperm collection and cryopreservation protocols developed in a model amphibian to three threatened anuran species targeted for biobanking management. (January 2023) - Burger, Isabella J.; Chen, Li-Dunn; Lampert, Shaina S.; Kouba, Carrie K.; Barber, Diane; Smith, Dustin; Cobos, Cassidi; Kouba, Andrew J.
Abstract: The challenge of replicating environmental cues in amphibian captive assurance colonies has been shown to be one of the contributing factors leading to limited breeding success. To circumvent this challenge, assisted reproductive technologies (ART) have been developed in model organisms and can now be applied to at-risk species. This study tested the transferability of cryopreservation protocols developed in the Fowler's toad ( Anaxyrus fowleri ) to three threatened anurans, the Chiricahua leopard frog ( Lithobates chiricahuensis ), Puerto Rican crested toad ( Peltophryne lemur ), and Houston toad ( Anaxyrus houstonensis ). Males were administered human chorionic gonadotropin and/or gonadotropin releasing hormone-analog to elicit spermiation, and spermic urine was collected and analyzed for motility. Samples were cryopreserved with 10 %  N, N -dimethylformamide + 10 % trehalose + 0.25 % bovine serum albumin and frozen at two rates, −32 to −45 °C/min and − 20 to −29 °C/min. Results show that sperm frozen at −32 to −45 °C/min recovered significantly higher post-thaw sperm motility than −20 to −29 °C/min for P. lemur ( p =  0.04) and L. chiricahuensis ( p  = 0.03). When compared across species, L. chiricahuensis had significantly higher post-thaw motility at both freezing rates ( p  < 0.05) than the other species, yet there was no difference between sperm motility between the three bufonid species for either freezing rate ( p  > 0.06). These results indicate that transferability of a cryopreservation protocol between species is possible, and differences in sensitivity and response to cryopreservation may exist between genera.